Digital Marketing Communication in Developing Countries - Rrustemi, Visar; Podvorica, Ganimete; Jusufi, Gezim (LeXonomica, 2020)
Digital marketing has made significant progress in recent years, in all countries, both developed and developing. Many local and international companies have largely placed their marketing activities in the digital environment. Now, the COVID-19 pandemic has made it even more important for many companies and consumers to conduct marketing, buying and selling activities through social media. Like companies, consumers are changing their buying behaviors by focusing more on social media, from which they are providing the necessary and sufficient information about all the products and services that are marketed online. This paper is of particular importance because it addresses the issue of digital marketing activities in the Western Balkans region, specifically the behavior of consumers from countries of this region on social media. From the results of the paper it can be concluded that consumers from these countries are quite engaged in social media, where they receive the necessary information for different products and services, follow the activities of different companies, etc.